Melampaui Toleransi: Studi terhadap Literasi Keagamaan Lintas Budaya - Afifur Rochman Sya'rani (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2025)
In an attempt to manage religious difference, this study focusses on a theoretical and practical evaluation of the idea of religious literacy. Since it introduces an interreligious educational approach and practice, the idea of religious literacy is regarded as important for addressing religious diversity. This study poses the following questions: how is the idea of religious literacy conceptualized? In what ways is religious literacy taught and practiced in Indonesia? This study uses a case study methodology and is qualitative in nature. This research looked at the Leimena Institute's Cross-Cultural Religious Literacy program. The goal of cross-cultural religious literacy is to create an environment where religious believers may interact and work together. This research finds that Cross-Cultural Religious Literacy is a crucial approach to fostering interreligious learning that goes beyond tolerance and towards interfaith involvement and cooperation in the face of rising religiously motivated violent extremism and religious division. Through the components of three competencies and three skills, as well as interdisciplinary approaches to understanding and teaching about religion. Cross-Cultural Religious Literacy promotes four dimensions of religious literacy: factual, procedural, conceptual, and metacognitive knowledge.